Development of a new LC-MS method for accurate and sensitive determination of 33 pyrrolizidine and 21 tropane alkaloids in plant-based food matrices - Dzuman, Zbynek; Jonatova, Petra; Stranska-Zachariasova, Milena; Prusova, Nela; Brabenec, Ondrej; Novakova, Alena; Fenclova, Marie; Hajslova, Jana (Analytical and bioanalytical chemistry, 2020)
Setting of maximum limits for a number of plant alkaloids is under discussion in the EU. The novel method developed and optimized in this study enables simultaneous determination of 21 tropane alkaloids (TAs) and 33 pyrrolizidine (PAs) together with their N-oxides (PANOs). For analysis of aqueous-methanolic extract, reversed phase ultra-high-performance liquid chromatography and tandem mass spectrometry (RP-U-HPLC-MS/MS) was employed. The method was validated for frequently contaminated matrices (i) sorghum, (ii) oregano, and (iii) mixed herbal tea. The recoveries at two spiking levels were in the range of 82-115%, 80-106%, and 78-117%, respectively, and repeatabilities were less than 19% for all analyte/matrix combinations. As regards the achieved limits of quantification (LOQ), their values were in the range of 0.5-10 μg kg-1. The crucial problem encountered during method development, co-elution of multiple groups of isomeric alkaloids, was overcome by subsequent sample separation in the second chromatographic system, hydrophilic interaction liquid chromatography (HILIC), providing different separation selectivity. Lycopsamine, echinatine, and indicine (co-elution group 1) and N-oxides of indicine and intermedine (co-elution group 2), which could not be resolved on the commonly used RP column, were possible to separate fully by using the HILIC system.
Keywords: Food Contamination; Tandem Mass Spectrometry; tropany; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Pyrrolizidine Alkaloids; alkaloidy; rostliny; isomerie; kontaminace potravin; reprodukovatelnost výsledků; limita detekce; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Alkaloids; Isomerism; Plants; Limit of Detection; pyrrolizidinové alkaloidy; Tropanes